A method for quantitatively testing water vapor side permeation and application thereof

CN122944283APending Publication Date: 2026-10-20SUZHOU INST OF NANO TECH & NANO BIONICS CHINESE ACEDEMY OF SCI
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202510449643.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-04-10
Publication Date
2026-10-20

AI Technical Summary

Technical Problem

然而,现有技术尚无法有效区分这两种渗透过程,也没有定量测试的手段,这限制了封装材料和工艺的进一步优化,从而影响了电子器件的可靠性与寿命

Benefits of technology

[0018]基于上述技术方案,与现有技术相比,本发明的有益效果至少包括:

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
  • Figure SMS_3
    Figure SMS_3
Patent Text Reader

Abstract

This invention provides a method for quantitatively differentiating water vapor lateral permeation and its application. The method includes: providing a test structure; conducting a water vapor erosion test, recording the relationship between water vapor propagation distance and time, and calculating the apparent diffusion rate; fitting the relationship between the apparent diffusion rate and thickness to obtain the water vapor diffusion coefficient and water vapor saturation concentration; and calculating the adhesive permeation amount and interfacial permeation amount based on Fick's second law. This invention constructs test devices of different thicknesses for testing, fitting the relationship between adhesive thickness and apparent diffusion rate to obtain the water vapor diffusion coefficient and water vapor saturation concentration, and then calculating the adhesive permeation amount and interfacial permeation amount. It is the first to propose a novel test method capable of quantitatively analyzing two water vapor permeation pathways, enabling scientific analysis of water vapor lateral permeation in cover plate encapsulation. This provides a theoretical basis for improving the moisture resistance, stability, and reliability of electronic devices, thereby extending their service life.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of electronic product packaging technology, and in particular to a method for distinguishing and quantifying water vapor side penetration and its application. Background Technology

[0002] Cover encapsulation technology is an important means of protecting electronic devices from moisture corrosion and is widely used in electronic equipment manufacturing. During the use of electronic devices, environmental factors such as moisture and humidity often lead to device failure, especially under high temperature and high humidity conditions, where moisture penetration can cause serious problems. Therefore, to ensure the long-term reliability of electronic devices, it is essential to effectively prevent moisture penetration through encapsulation technology.

[0003] As electronic devices continue to evolve towards miniaturization, flexibility, and high performance, the requirements for packaging technology are also increasing. This makes the study of moisture permeation paths and quantitative testing methods particularly important. Lateral moisture permeation is considered the main path for moisture permeation in cover plate packaging. Specifically, there are two main lateral moisture permeation paths: one is through the adhesive sublayer itself, and the other is through the interface between the adhesive and the packaged device.

[0004] To effectively improve encapsulation performance, it's necessary to understand the quantitative proportions of moisture in the two permeation pathways mentioned above during actual applications. If the adhesive layer is the primary permeator, then the moisture permeability needs to be reduced by improving the composition of the adhesive layer. Conversely, for moisture permeation dominated by the adhesive, the bonding strength between the adhesive layer and the interface needs to be improved to enhance the encapsulation effect.

[0005] Although the industry recognizes that there are two permeation pathways for moisture lateral penetration, there are currently no mature and effective methods for detecting and quantifying these two pathways. Extensive literature review has revealed no publicly available patents, journals, or books providing technical solutions that can accurately distinguish and quantify these two permeation pathways. Existing testing methods mostly focus on evaluating the overall moisture permeability and macroscopic characteristics of moisture permeation within the package, lacking detailed analysis of specific permeation pathways. Therefore, current technologies struggle to accurately distinguish between the two permeation pathways and lack quantitative methods to analyze the specific process of moisture permeation.

[0006] In other words, establishing a quantitative method to characterize the pathways through which moisture permeates during cover encapsulation is of great practical significance. However, current technologies cannot effectively distinguish between these two permeation processes, nor do they have quantitative testing methods. This limits further optimization of encapsulation materials and processes, thereby affecting the reliability and lifespan of electronic devices. Summary of the Invention

[0007] To address the shortcomings of existing technologies, the present invention aims to provide a method for distinguishing and quantifying water vapor lateral permeation and its application.

[0008] To achieve the aforementioned objectives, the technical solution adopted by this invention includes:

[0009] In a first aspect, the present invention provides a method for distinguishing and quantifying water vapor lateral permeation, comprising:

[0010] A test structure is provided, comprising a substrate, a moisture reaction layer, an adhesive encapsulation layer, and a waterproof cover layer. The moisture reaction layer is tightly bonded to the substrate and covered by the adhesive encapsulation layer, with the coverage area of ​​the adhesive encapsulation layer being larger than the bonding area of ​​the moisture reaction layer. The adhesive encapsulation layer is divided into an interface sublayer and an adhesive sublayer, with the interface sublayer located between the adhesive sublayer and the substrate outside the bonding area. The moisture reaction layer undergoes changes in optical properties upon contact with water. The waterproof cover layer completely covers the surface of the adhesive encapsulation layer, and the sides of the adhesive encapsulation layer are exposed.

[0011] Water vapor erosion tests were conducted on multiple test structures with different thicknesses of binder sublayers under selected conditions. The relationship between the propagation distance and time from the boundary of the optical property change region caused by water vapor intrusion into the water vapor reaction layer and the center of the water vapor reaction layer was recorded. The apparent diffusion rate corresponding to the thickness of different binder sublayers was calculated.

[0012] Based on the relationship between the apparent diffusion rate and the thickness of the binder sublayer, the water vapor diffusion coefficient and water vapor saturation concentration of the binder sublayer are obtained by fitting.

[0013] Using the water vapor diffusion coefficient and water vapor saturation concentration, the adhesive permeation and interface permeation are calculated based on Fick's second law, respectively. The adhesive permeation refers to the permeation caused by water vapor diffusion through the adhesive encapsulation layer itself, and the interface permeation refers to the permeation caused by water vapor diffusion through the interface between the adhesive encapsulation layer and the substrate.

[0014] Secondly, the present invention also provides a specific application of the above-mentioned differentiation quantification test method, namely, an iterative improvement method for adhesive encapsulation structures, which includes:

[0015] Provide the packaging structure to be tested, and use the above-mentioned differentiation and quantification test method to test it to obtain the adhesive penetration amount and the interface penetration amount;

[0016] When the adhesive penetration amount is dominant, improve the composition of the adhesive encapsulation layer in the encapsulation structure under test;

[0017] When the interface penetration amount is dominant, it improves the interfacial bonding performance between the adhesive encapsulation layer and the substrate in the encapsulation structure under test.

[0018] Based on the above technical solution, compared with the prior art, the beneficial effects of the present invention include at least the following:

[0019] The quantitative testing method provided by this invention tests the water vapor permeation rate by constructing test devices of different thicknesses. It obtains the water vapor diffusion coefficient and water vapor saturation concentration by fitting the relationship between adhesive thickness and apparent diffusion rate, and then calculates the adhesive permeation amount and interfacial permeation amount. This invention is the first to propose a novel testing method that can quantitatively analyze two water vapor permeation pathways. It can scientifically analyze the side permeation of water vapor in cover plate packaging, providing a theoretical basis for improving the moisture resistance, stability and reliability of electronic devices, and extending their service life.

[0020] The above description is merely an overview of the technical solution of the present invention. In order to enable those skilled in the art to better understand the technical means of this application and to implement it in accordance with the contents of the specification, the preferred embodiments of the present invention are described below in conjunction with detailed drawings. Attached Figure Description

[0021] Figure 1 This is a schematic diagram of a water vapor side infiltration model provided in a typical embodiment of the present invention. Detailed Implementation

[0022] The main drawback of existing technologies is their inability to distinguish whether moisture permeates through the adhesive sublayer or through the interface between the adhesive and the encapsulated device, and they also cannot quantitatively test these two permeation processes. The root cause of this problem is the complexity of the moisture permeation process, involving microscopic mass transport and interactions. Furthermore, these two permeation paths are often intertwined in practice, making it difficult for existing conventional detection methods to accurately distinguish and quantify them. In short, existing technologies cannot effectively distinguish and quantify the moisture permeation process from the adhesive sublayer to the encapsulated device interface primarily because existing models and testing methods lack precise descriptions and quantification methods for lateral permeation paths.

[0023] In view of the shortcomings of the prior art, the inventors of this invention, through long-term research and extensive practice, have proposed the technical solution of this invention. The following will further explain and illustrate this technical solution, its implementation process, and its principles.

[0024] To address this issue, this invention proposes a testing method based on the optical calcium film method. By measuring the correlation between the rate of corrosion retreat at the edge of the calcium film during aging and the thickness of the adhesive layer, the proportion of water vapor permeation in the two paths can be accurately calculated, thereby achieving quantitative analysis of the water vapor lateral permeation process.

[0025] The purpose of this invention is to develop a testing method to accurately distinguish and quantitatively test two permeation paths, providing strong support for optimizing packaging materials and processes. By implementing this technical solution, the lateral permeation of moisture in cover plate packaging can be scientifically analyzed, providing a theoretical basis for improving the moisture resistance, stability, and reliability of electronic devices, while extending their service life.

[0026] Many specific details are set forth in the following description in order to provide a full understanding of the invention. However, the invention may also be practiced in other ways different from those described herein, and therefore the scope of protection of the invention is not limited to the specific embodiments disclosed below.

[0027] Moreover, relational terms such as “first” and “second” are used merely to distinguish one component or method step from another that has the same name, and do not necessarily require or imply any such actual relationship or order between these components or method steps.

[0028] This invention provides a method for distinguishing and quantifying water vapor lateral infiltration, comprising the following steps:

[0029] A test structure as shown in the figure is provided. The test structure includes a substrate, a moisture reaction layer, an adhesive encapsulation layer, and a waterproof cover layer. The moisture reaction layer is closely adhered to the substrate and covered by the adhesive encapsulation layer. The coverage area of ​​the adhesive encapsulation layer is larger than the adhesion area of ​​the moisture reaction layer. The adhesive encapsulation layer is divided into an interface sublayer and an adhesive sublayer. The interface sublayer is located between the adhesive sublayer and the substrate outside the adhesion area. The moisture reaction layer undergoes changes in optical properties upon contact with water. The waterproof cover layer completely covers the surface of the adhesive encapsulation layer, and the sides of the adhesive encapsulation layer are exposed.

[0030] Water vapor erosion tests were conducted on multiple test structures with different thicknesses of binder sublayers under selected conditions. The relationship between the propagation distance and time from the boundary of the optical property change region caused by water vapor intrusion into the water vapor reaction layer and the center of the water vapor reaction layer was recorded. The apparent diffusion rate corresponding to the thickness of different binder sublayers was calculated.

[0031] Based on the relationship between the apparent diffusion rate and the thickness of the binder sublayer, the water vapor diffusion coefficient and water vapor saturation concentration of the binder sublayer are obtained by fitting.

[0032] Using the water vapor diffusion coefficient and water vapor saturation concentration, the adhesive permeation and interface permeation are calculated based on Fick's second law, respectively. The adhesive permeation refers to the permeation caused by water vapor diffusion through the adhesive encapsulation layer itself, and the interface permeation refers to the permeation caused by water vapor diffusion through the interface between the adhesive encapsulation layer and the substrate.

[0033] It should be noted that the aforementioned interface sublayer refers to a material layer whose water vapor diffusion properties are significantly different from those of the adhesive sublayer due to insufficient adhesion between the adhesive and the substrate. In the theoretical model, it is a hypothetical layer, and its specific thickness does not affect the calculation of interface penetration and adhesive penetration.

[0034] In some implementations, the thickness of the interface sublayer is lower than the thickness of the water vapor reaction layer. Theoretically, the interface sublayer should be thinner than the water vapor reaction layer. The interface sublayer is a hypothetical layer, and its thickness cannot be accurately measured. The hypothetical thickness of this layer in the technical solution of this invention is for the convenience of subsequent modeling and calculation; this also means that the thickness of the interface sublayer is essentially a fuzzy concept, but its influence on water vapor diffusion is clear, and necessary assumptions need to be made to achieve quantitative analysis.

[0035] In some embodiments, the thickness of the interfacial sublayer is the same in multiple test structures. The thickness of the interfacial sublayer is only related to the adhesive strength; therefore, the thickness of the interfacial sublayer is consistent in multiple samples of different thicknesses prepared under the same conditions. The thickness of the interfacial sublayer does not need to be specifically measured, as its effect on water vapor diffusion is comprehensive, involving the combined effects of thickness, saturation concentration, and diffusion coefficient, and cannot be discussed separately. Therefore, after modeling with its assumed thickness, the final thickness will be canceled out, and the calculation of the permeation of the cross-section and adhesive is not dependent on the specific value of this thickness.

[0036] Regarding the thickness of each layer in the theoretical model, in some implementations, the thickness of the interface sublayer ranges from 0 to 1 μm.

[0037] In some embodiments, the thickness of the adhesive sublayer ranges from 0.1 to 1000 μm.

[0038] In some embodiments, the thickness of the water vapor reaction layer ranges from 0.01 to 1 μm.

[0039] The thickness of each layer mentioned above is a theoretical preset, and the specific values ​​are not the focus of this invention. In practical applications, the thickness range is not limited to the above-mentioned thickness range.

[0040] In some implementations, the apparent diffusion rate is calculated using the following formula:

[0041]

[0042] Wherein, K represents the apparent diffusion rate, T0 represents the initial time from the side of the adhesive encapsulation layer to the edge of the moisture reaction layer, ΔT represents the time interval from the initial time to when the moisture intrusion in the moisture reaction layer reaches the propagation distance, L0 represents the distance from the side of the adhesive encapsulation layer to the edge of the moisture reaction layer, and ΔL represents the propagation distance.

[0043] In some implementations, the fitting formulas for the water vapor diffusion coefficient and the water vapor saturation concentration are expressed as follows:

[0044]

[0045] Among them, h A N0 represents the thickness of the adhesive sublayer, and D represents the amount of water absorbed per unit volume of the water vapor reaction layer. I C represents the interfacial diffusion coefficient of water vapor in the interfacial sublayer. SI h represents the interface saturation concentration of the interface sublayer. I D represents the thickness of the interface sublayer. A C represents the water vapor diffusion coefficient of the adhesive sublayer. SA This indicates the water vapor saturation concentration of the adhesive sublayer.

[0046] In some implementations, the adhesive penetration amount and interfacial penetration amount are calculated as follows:

[0047]

[0048] Among them, J A J represents the amount of adhesive penetration. I The value represents the amount of interfacial penetration, and erfc(·) represents the complementary error function.

[0049] In some embodiments, the relationship between the adhesive penetration amount and the interfacial penetration amount is expressed as:

[0050]

[0051] in, The total water vapor infiltration rate is represented by Q, where Q represents the molar ratio of water to the water vapor reaction layer, and h represents the total water vapor infiltration rate. R ρ represents the thickness of the water vapor reaction layer. R M represents the density of the water vapor reaction layer. R This indicates the relative atomic and molecular mass of the material of the water vapor reaction layer.

[0052] In some implementations, the substrate material includes any one or more combinations of inorganic glass, plexiglass, barrier film, and metal, wherein the metal may be, for example, copper or aluminum.

[0053] In some implementations, the material of the water vapor reaction layer includes any one or more combinations of water-reactive materials such as metallic calcium, perovskite, and P3HT, and is not limited to these.

[0054] In some implementations, the waterproof covering layer is made of any one or a combination of two or more waterproof materials such as aluminum, glass, silica, and silicon nitride, and is not limited thereto.

[0055] In a typical exemplary scheme, the model building and derivation process of the above-mentioned distinguishing quantification test method includes:

[0056] In the lateral diffusion model of water vapor, we use calcium corrosion and Fick's second law to establish the lateral diffusion equation of water vapor. Using a calcium film as the water vapor reaction layer, the theoretical assumptions are: (1) the thickness of the calcium film is thin enough that the absorption of water by the calcium film does not affect the kinetic process of water vapor diffusion; (2) the reaction rate between calcium and water is fast enough that the water above the calcium film can react with calcium quickly without further diffusion.

[0057] At any given time, the contribution of calcium film corrosion mainly comes from two parts: the binder sublayer and the interface sublayer, and these contributions can be calculated independently. It is assumed that the diffusion process of water vapor through the binder and interface follows Fick's second law. For the one-dimensional (1D) case, Fick's second law states:

[0058]

[0059] Where C is the concentration of the diffusing substance, D is the diffusion coefficient of the substance, x is the diffusion distance, and t is the diffusion time.

[0060] The concentration distribution of water vapor can be represented by a Gaussian error function:

[0061]

[0062] The water vapor concentration distribution in the binder sublayer and the interfacial sublayer can be expressed as:

[0063]

[0064] Among them, C SA and C SI These are the saturated water vapor concentrations at the bonding surface and the interface, respectively, D. A and D I These represent the diffusion constants of water vapor through the binder and the interface, respectively.

[0065] During the time (ΔT) during which the water vapor erosion boundary of calcium moves from L0 to L0+ΔL, the total amount of water vapor corroding calcium (in mol·m⁻¹) is... -1 (in units) can be calculated as:

[0066]

[0067] Among them, h Ca It is the thickness of the calcium film, ρ Ca It is the density of calcium, M Ca It is the molar mass of calcium, calculated based on 1 mol of calcium absorbing 1 mol of water. If other materials are used, adjustments need to be made based on their known chemical properties.

[0068] Within the time interval ΔT, through the overall adhesive (J) A ) and interface (J I (Unit: moles·m^-1) The total amount of water vapor reaching the edge of the calcium film can be calculated as follows:

[0069]

[0070] Among them, h A It is the thickness of the adhesive sublayer, h I It is the thickness of the interface sublayer.

[0071] Therefore, the volume diffusion and interfacial diffusion of water vapor can be expressed as follows:

[0072]

[0073] Since calcium corrosion originates solely from water vapor erosion, the total amount of water vapor used for calcium corrosion should equal the total amount of water vapor passing through the binder and interface, i.e.:

[0074]

[0075] During water vapor diffusion, the diffusion distance x and the diffusion time t follow the following relationship:

[0076]

[0077] K is defined as the apparent diffusion rate.

[0078] Therefore:

[0079]

[0080] We can obtain:

[0081]

[0082] Substituting equation (14) into equations (8) and (9), we get:

[0083]

[0084] in:

[0085]

[0086] Therefore, we can conclude that:

[0087]

[0088] Combining equations (5), (10), (18), and (19), we obtain:

[0089]

[0090] Substituting equation (13) into equation (20) and rearranging, we get:

[0091]

[0092] Considering Equation (21) can be simplified to:

[0093]

[0094] To facilitate subsequent calculations and experimental fitting, using the first-order approximation of Taylor expansion, equation (22) can be simplified to:

[0095]

[0096] In the above equations, equation (23) can be used to fit the results of subsequent experiments. It can be used to fit the apparent permeability K value obtained by optical calcium film testing under different binder sublayer thicknesses to obtain the water vapor diffusion coefficient D of the binder sublayer. A and the water vapor saturation concentration C of the binder sublayer SA Equations (18) and (19) can be used to determine the water vapor diffusion coefficient D of the known binder sublayer. A and the water vapor saturation concentration C of the binder sublayer SA Given the corresponding K value obtained from the test, the contribution of water vapor diffused in the binder sublayer and the interface sublayer to the corrosion of the calcium film is calculated respectively.

[0097] The specific testing method in practical applications is as follows: A calcium film of a specific shape (e.g., square, 100 nm) is deposited on a substrate identical to the one being tested. An adhesive is used to bond the encapsulation cover to the substrate to encapsulate the calcium film. The encapsulated calcium film is placed in a constant temperature and humidity chamber with fixed humidity, and the corrosion of the calcium film is recorded using a camera. The relationship between the edge corrosion displacement of the calcium film and time is extracted and plotted. Since the reaction between the calcium film and water is very rapid, the corrosion of the calcium film can be used to characterize the diffusion process of water vapor. Because the diffusion distance of water vapor is proportional to the square root of time, the displacement of the edge corrosion of the calcium film is also proportional to the square root of time. The slope of the linear relationship is defined as the apparent permeation rate K. By changing the thickness of the adhesive sublayer (e.g., from 100 μm to 900 μm) and repeating the above experiment, the relationship between the apparent permeation rate and the thickness of the adhesive sublayer can be obtained. By fitting this relationship using equation (), the water vapor diffusion coefficient D of the adhesive sublayer can be obtained. A and the water vapor saturation concentration C of the binder sublayer SA Equations (18) and (19) can be used to calculate the water vapor diffusion coefficient D of a known binder sublayer. A and the water vapor saturation concentration C of the binder sublayer SA Given the K value obtained from the test for the corresponding thickness, the contribution of water vapor diffused in the binder sublayer and the interface sublayer to the corrosion of the calcium film is calculated respectively.

[0098] As an application of the above technical solution, a second aspect of the present invention also provides an iterative improvement method for an adhesive encapsulation structure, which includes the following steps:

[0099] Provide a package structure to be tested, and use the differentiation and quantification test method provided in any of the above embodiments to test it to obtain the adhesive penetration amount and the interface penetration amount.

[0100] When the adhesive penetration amount is dominant, improve the composition of the adhesive encapsulation layer in the encapsulation structure under test;

[0101] When the interface penetration amount is dominant, it improves the interfacial bonding performance between the adhesive encapsulation layer and the substrate in the encapsulation structure under test.

[0102] The technical solution of the present invention will be further described in detail below through several embodiments and in conjunction with the accompanying drawings. However, the selected embodiments are only for illustrating the present invention and do not limit the scope of the present invention.

[0103] Example 1

[0104] This embodiment uses the optical calcium film method provided in the above specific implementation to test the performance of tape encapsulation with different adhesive encapsulation layers and different adhesive encapsulation layer thicknesses, in order to distinguish the proportion of water vapor diffusion from the interface and the adhesive sublayer, so as to conduct targeted screening and optimization of the tape adhesive.

[0105] The adhesive materials used in the tapes include acrylates, butyl rubber, epoxy resins, silicone resins, phenolic resins, amino resins, polyurethanes, etc., all of which can quantitatively characterize the penetration ratio of the interface and the adhesive layer itself.

[0106] Example 2

[0107] The encapsulation performance of different adhesive layers in cover plate packaging was tested using the aforementioned optical calcium film method to distinguish the proportion of water vapor diffusion from the interface sublayer and the adhesive sublayer, so as to selectively screen and optimize the adhesive used.

[0108] The adhesive materials used in the tapes include acrylates, butyl rubber, epoxy resins, silicone resins, phenolic resins, amino resins, polyurethanes, etc., all of which can quantitatively characterize the penetration ratio of the interface and the adhesive layer itself.

[0109] Example 3

[0110] The coated adhesive was tested using the aforementioned optical calcium film method to distinguish the proportion of water vapor diffusion from the interface and the adhesive layer, and the water vapor diffusion coefficient D of the adhesive layer could be measured. A and the water vapor saturation concentration C of the adhesive layer SA .

[0111] Based on the above embodiments, it is clear that the differentiation and quantification test method provided by the embodiments of the present invention tests the water vapor permeation rate by constructing test devices of different thicknesses, and obtains the water vapor diffusion coefficient and water vapor saturation concentration by fitting the relationship between adhesive thickness and apparent diffusion rate, and then calculates the adhesive permeation amount and interface permeation amount. For the first time, a novel test method capable of quantifying and analyzing two water vapor permeation pathways has been proposed, which can scientifically analyze the side permeation of water vapor in the cover plate encapsulation, and provide a theoretical basis for improving the moisture resistance, stability and reliability of electronic devices, so as to extend their service life.

[0112] It should be understood that the above embodiments are merely illustrative of the technical concept and features of the present invention, and are intended to enable those skilled in the art to understand the content of the present invention and implement it accordingly. They should not be construed as limiting the scope of protection of the present invention. All equivalent changes or modifications made in accordance with the spirit and essence of the present invention should be covered within the scope of protection of the present invention.

Claims

1. A method for distinguishing and quantifying water vapor lateral infiltration, characterized in that, include: A test structure is provided, comprising a substrate, a moisture reaction layer, an adhesive encapsulation layer, and a waterproof cover layer. The moisture reaction layer is tightly bonded to the substrate and covered by the adhesive encapsulation layer, with the coverage area of ​​the adhesive encapsulation layer being larger than the bonding area of ​​the moisture reaction layer. The adhesive encapsulation layer is divided into an interface sublayer and an adhesive sublayer, with the interface sublayer located between the adhesive sublayer and the substrate outside the bonding area. The moisture reaction layer undergoes changes in optical properties upon contact with water. The waterproof cover layer completely covers the surface of the adhesive encapsulation layer, and the sides of the adhesive encapsulation layer are exposed. Water vapor erosion tests were conducted on multiple test structures with different thicknesses of binder sublayers under selected conditions. The relationship between the propagation distance and time from the boundary of the optical property change region caused by water vapor intrusion into the water vapor reaction layer and the center of the water vapor reaction layer was recorded. The apparent diffusion rate corresponding to the thickness of different binder sublayers was calculated. Based on the relationship between the apparent diffusion rate and the thickness of the binder sublayer, the water vapor diffusion coefficient and water vapor saturation concentration of the binder sublayer are obtained by fitting. Using the water vapor diffusion coefficient and water vapor saturation concentration, the adhesive permeation and interface permeation are calculated based on Fick's second law, respectively. The adhesive permeation refers to the permeation caused by water vapor diffusion through the adhesive encapsulation layer itself, and the interface permeation refers to the permeation caused by water vapor diffusion through the interface between the adhesive encapsulation layer and the substrate.

2. The distinguishing quantification test method according to claim 1, characterized in that, The thickness of the interface sublayer is lower than the thickness of the water vapor reaction layer.

3. The distinguishing quantification test method according to claim 2, characterized in that, The thickness of the interface sublayer is the same in multiple of the test structures.

4. The distinguishing quantification test method according to claim 2, characterized in that, The thickness of the interface sublayer ranges from 0 to 1 μm; And / or, the thickness of the adhesive sublayer ranges from 0.1 to 1000 μm; And / or, the thickness of the adhesive sublayer ranges from 0.1 to 1000 μm.

5. The distinguishing quantification test method according to claim 1, characterized in that, The formula for calculating the apparent diffusion rate is as follows: Wherein, K represents the apparent diffusion rate, T0 represents the initial time from the side of the adhesive encapsulation layer to the edge of the moisture reaction layer, ΔT represents the time interval from the initial time to when the moisture intrusion in the moisture reaction layer reaches the propagation distance, L0 represents the distance from the side of the adhesive encapsulation layer to the edge of the moisture reaction layer, and ΔL represents the propagation distance.

6. The distinguishing quantification test method according to claim 5, characterized in that, The fitting formulas for the water vapor diffusion coefficient and the water vapor saturation concentration are expressed as follows: Among them, h A The thickness of the adhesive sublayer is indicated by N0, which represents the amount of water absorbed per unit volume of the water vapor reaction layer, and D is the thickness of the adhesive sublayer. I C represents the interfacial diffusion coefficient of water vapor in the interfacial sublayer. SI The table shows the interface saturation concentration of the interface sublayer, h. I D represents the thickness of the interface sublayer. A C represents the water vapor diffusion coefficient of the adhesive sublayer. SA This indicates the water vapor saturation concentration of the adhesive sublayer.

7. The distinguishing quantification test method according to claim 6, characterized in that, The calculation methods for the adhesive penetration and interfacial penetration are expressed as follows: Among them, J A J represents the amount of adhesive penetration. I The value represents the amount of interfacial penetration, and erfc(·) represents the complementary error function.

8. The distinguishing quantification test method according to claim 6, characterized in that, The relationship between the adhesive penetration and the interfacial penetration is expressed as follows: in, The total water vapor infiltration rate is represented by Q, where Q represents the molar ratio of water to the water vapor reaction layer, and h represents the total water vapor infiltration rate. R ρ represents the thickness of the water vapor reaction layer. R M represents the density of the water vapor reaction layer. R This indicates the relative atomic / molecular mass of the material in the water vapor reaction layer.

9. The distinguishing quantification test method according to claim 1, characterized in that, The substrate material includes any one or a combination of two or more of inorganic glass, plexiglass, barrier film, and metal. And / or, the material of the water vapor reaction layer includes any one or a combination of two or more of metallic calcium, perovskite, and P3HT; And / or, the material of the waterproof covering layer includes any one or a combination of two or more of aluminum, glass, silicon dioxide, and silicon nitride.

10. An iterative improvement method for an adhesive encapsulation structure, characterized in that, include: Provide a package structure to be tested, and use the differentiation and quantification test method described in any one of claims 1-9 to test it and obtain the adhesive penetration amount and the interface penetration amount; When the adhesive penetration amount is dominant, improve the composition of the adhesive encapsulation layer in the encapsulation structure under test; When the interface penetration amount is dominant, it improves the interfacial bonding performance between the adhesive encapsulation layer and the substrate in the encapsulation structure under test.